Terapia transfusional: criterios de indicaciones de componentes sanguíneos - Larrondo L., Milton; Figueroa M. , Gastón (Revista Hospital Clínico Universidad de Chile, 2007)
The new development in transfusion medicine has allowed that blood component would be available safely for patients. However, like other medical therapies, we should establish clearly the indications based on the best benefit/risk relationship. In the following paragraphs the indications for red cells, platelets, fresh frozen plasma and cryoprecipitate will be shown. Finally, the risks and adverse events to blood transfusion will be reviewed.